2019
DOI: 10.3390/w11020251
|View full text |Cite
|
Sign up to set email alerts
|

Communications on Technological Innovations: Potable Water Reuse

Abstract: Water scarcity has prompted an increasing number of cities to look for non-conventional sources of clean water. One of these sources is reused water, or highly treated reclaimed or recycled wastewater, a worthy addition to the portfolio of water-resource alternatives that increasing cities are considering in view of demographic and environmental changes. In this paper, we analyse communications from the media, policymakers and utility managers on the technology used to produce reused water for potable purposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Leong (2016) suggests that allowing for dialogue between expert and public opinion produces rational clarity. Evidence indicates that technocratically driven water reuse schemes that treat the public as subjects rather than agents are likely to flounder; studies have ascribed the failure of water reuse schemes such as Toowoomba and San Diego to a (CA, USA) and Queensland (Australia) suggests that droughts and water scarcity have been instrumental in changing the perceptions and attitudes of policy-makers and communities to be more willing to consider recycled water for potable use (see Tortajada & Nambiar 2019). Given these contrasting outcomes, what then are the specific conditions under which the public might support water reuse?…”
Section: Disgust As More Than Simple Revulsionmentioning
confidence: 99%
“…Leong (2016) suggests that allowing for dialogue between expert and public opinion produces rational clarity. Evidence indicates that technocratically driven water reuse schemes that treat the public as subjects rather than agents are likely to flounder; studies have ascribed the failure of water reuse schemes such as Toowoomba and San Diego to a (CA, USA) and Queensland (Australia) suggests that droughts and water scarcity have been instrumental in changing the perceptions and attitudes of policy-makers and communities to be more willing to consider recycled water for potable use (see Tortajada & Nambiar 2019). Given these contrasting outcomes, what then are the specific conditions under which the public might support water reuse?…”
Section: Disgust As More Than Simple Revulsionmentioning
confidence: 99%
“…Recent advancements in treatment technologies has enabled the reuse of wastewater for drinking purposes. Among the most successful potable reuse projects that are acknowledged globally include the United States' Orange County Groundwater Replenishment System and Singapore's NEWater [62,63]. Wastewater reuse has become a widely acceptable approach for relieving water stress in several regions around the world; however, recent investigations showed that the use of reclaimed wastewater for irrigation can lead to PPCP contamination in soils [64,65].…”
Section: Ppcp Routes In Soils Sediments and Biosolidsmentioning
confidence: 99%
“…These efforts largely were aimed at generating public awareness and knowledge of recycled potable water (e.g., early engagement with media and creation of a visitor's center for NEWater; Kheng & Toh, 2012; Lee & Tan, 2016). These efforts resulted in overall support for the direct recycled potable water program, with some studies estimating 98% approval among citizens of Singapore for NEWater (Tortajada & Nambiar, 2019).…”
Section: Psychological Factors Associated With Acceptance Of Recycled Watermentioning
confidence: 99%